2019
DOI: 10.3390/foods8090394
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyunsaturated Fatty Acids Are Associated with Blood Pressure and Hypertension over 10-Years in Black South African Adults Undergoing Nutritional Transition

Abstract: Nutritional transition in Africa is linked with increased blood pressure (BP). We examined 10-year fatty acid status and longitudinal associations between individual long-chain polyunsaturated fatty acids (PUFA), BP and status of hypertension (≥140/90 mmHg and/or medication use) in black South Africans. We included 300 adults (>30 years) participating in the Prospective Urban Rural Epidemiology study, and analysed data from three consecutive examinations (2005, 2010 and 2015 study years). Fatty acids in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The change in fatty acid biosynthesis can contribute to the pathogenesis of hypertension. Fatty acids, especially polyunsaturated fatty acids, are of rising importance as the potential biomarkers of hypertension . In our results, the level of adrenic acid (an intermediate of biosynthesis of unsaturated fatty acids) was significantly increased in the QIGLF group compared with that in the model group, and the increase ultimately led to vasodilation.…”
Section: Resultssupporting
confidence: 45%
“…The change in fatty acid biosynthesis can contribute to the pathogenesis of hypertension. Fatty acids, especially polyunsaturated fatty acids, are of rising importance as the potential biomarkers of hypertension . In our results, the level of adrenic acid (an intermediate of biosynthesis of unsaturated fatty acids) was significantly increased in the QIGLF group compared with that in the model group, and the increase ultimately led to vasodilation.…”
Section: Resultssupporting
confidence: 45%
“…Although nearly all measured fatty acids and amino acids were strongly related to BP in the cross-sectional analyses, none of them demonstrated any strong associations in the longitudinal analyses. Despite several prior studies reporting strong cross-sectional associations of fatty acids and amino acids with BP [ 30 35 ], the nature and strength of these associations warrants further study.…”
Section: Discussionmentioning
confidence: 86%
“…However, in a recent study from our group, we demonstrated that n-3 LCPUFA supplementation administered as therapy after TB infection lowered systemic and lung inflammation in Mtb- infected C3HeB/FeJ mice that did not receive TB drug treatment ( 38 ). Since some populations at risk for TB has low n-3 PUFA status ( 39 , 40 ), we also previously investigated the effects of n-3 PUFA supplementation on low vs. sufficient n-3 PUFA mice without TB drug treatment ( 41 ). In this earlier study without TB medication, low n-3 PUFA status mice reacted differently and showed no benefit to supplementation after TB infection than mice with a sufficient n-3 PUFA status ( 35 , 41 ).…”
Section: Introductionmentioning
confidence: 99%